Analisis Latihan Keterampilan Teknik Dasar Sepak Bola untuk Atlet Pemula - Ahmad Atiq; Kumbul Selamet Budiyanto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to analyze the basic technical skills training of football, especially for novice athletes. This research was conducted in the city of Pontianak. The research population is football clubs or schools in the city of Pontianak. The method used in this research is descriptive research with a quantitative approach. The results of this study indicate that every soccer athlete, in this case beginners, still has a high weakness of 30%, 20% excess, 10% strength, and 40% chance. The conclusion of this study shows that the basic technical skills of novice football athletes in the city of Pontianak have a great opportunity to develop basic technical skills to the advanced level. If each athlete can provide competitiveness with the skills possessed by each athlete with a comprehensive, measurable, patterned and sustainable training program, this novice athlete will be good. Keywords: Analysis, Skills, Basic Techniques, Football